ESG impact on firm profitability, valuation and cost of debt - Nordic evidence - Manner, Tuomas (My University, 2018)
Burning of fossil fuels, using child labor or failing of internal control procedures are just a few examples of corporate responsibility matters that have become essential in today’s business world. Increasing amount of time and research have attempted to demonstrate the importance of corporate responsibility and how it drives financial value. The aim of this thesis is to examine this uncertainty. More explicitly, the research focuses on how corporate responsibility influence firm’s profitability, valuation and cost of debt. Environmental, social and governance (ESG) ratings have become typical indication of firm’s non-financial health and is utilized among professional investors. How effectively ESG scores are assessed by debt and equity markets is yet obscure and motivation of this thesis. ESG impact is tested by using pooled OLS regressions for 200 publicly listed firms in Nordic countries. Data is obtained from Thomson Reuters’ database and covers period from 2002 to 2016. Regression models test the overall impact of ESG as well as takes deeper focus in the best and worst ESG performers by using dummy variables. Empirical findings of this research indicate that ESG impact is significant and positive in firm’s market valuation. The results suggest that equity markets reward those firms with very high ESG performance and ignore those with very low ESG performance. Unlike previous literature and findings suggest, cost of debt is not lower for those with higher responsibility performance. Lastly, profitability seems to be positively associated with ESG rating as far as return on asset is used. Whereas ROE seems to be negatively associated with better ESG performance. These findings contribute to the previous literature by testing ESG impact only for Nordic countries and finds significant link between ESG ratings and firm’s market valuation.
Keywords: ESG; corporate responsibility; responsible investing; sustainability; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|